Correction to: Prevalence and correlates of transactional sex among women of low socioeconomic status in Portland, OR - Timothy W. Menza; Lauren Lipira; Amisha Bhattarai; Victoria Cali-De Leon; E. Roberto Orellana (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.